Hubungan Kekerabatan Beberapa Varietas Unggul Terpilih Tanaman Padi (Oryza sativa L.) Berdasarkan Marka Morfologi - Rahma Dini, Nanda Aulia; Azizah, Elia; Samaullah, MY; Susanto, Untung (JURNAL AGROPLASMA, 2023)
Differences and similarities in morphological characters in rice plants can be distinguished through characterization activities. Morphological characterization needs to be carried out to identify the superior characters that appear, especially characters related to the growth and development of rice plants which can increase the yield potential of rice. The results of the morphological characterization can be used to determine the close kinship and genetic distance between plants. This study aims to determine the kinship relationship and genetic distance formed in several selected superior varieties of rice plants. The research was conducted at the Experimental Garden of the Sukamandi Rice Research Center. The research method used is descriptive experimental method with a treatment of 44 varieties of rice, repeated 3 times. Observational data were analyzed using Ntsys 2.02 and 2.11 software with the UPGMA method. The results showed that several selected high yielding varieties had similarities in several morphological characters such as leaf width, leaf angle, leaf neck color, leaf midrib color, leaf tongue color and leaf tongue shape. The resulting similarity coefficient is 0.75 and seven groups with close kinship are formed. The genetic distance formed in several selected superior varieties of rice plants has a narrow diversity with a value of 0.25. The results for both parameters indicate that the resulting genetic diversity is small. This cannot be used as a cross parent but can be used as genetic material which is re-analyzed to increase its diversity.